The pharmacological screening of Piper betle L. - Crisolo, Eleanor Villafuerte
Piper betle L. (commonly known as betel pepper, ikmo or buyo ) used, especially by those people living in rural areas, as remedy for stomach aches, muscle pains and headaches. These pharmacological properties of betel pepper has not been proven scientifically. Hence, this study had come up with the following objectives: (1)to determine if Piper betle L. has medicinal value; (2)to test if Piper betle L. is toxic and (3)to determine the efficacy of Piper betle L. as an analgesic, antispasmodic and as an antibiotic. (p)Collected fresh of Piper betle L. were extracted using the extraction by soaking (cold percolation) method. To determine if the extract contains a pharmacologically active substance, phytochemical assay for alkaloids was performed. The extract was also screened on what concentrations it might be toxic to zoologic systems using the brine shrimp assay for toxicity. To test the extract's analgesic activity, acetic acid-induced writhing assay was used while charcoal tracing assay was performed to determine if it has antipasmodic property. Antimicrobial assay using the paper disc diffusion method was also done to verify the antimicrobial activity of the plant extract. (p)Results showed that Piper betle L. leaf contained a pharmacologically active substance, alkaloid. It was shown in the toxicity test that Piper betle L. leaf extract was estimated to be lethal to 50 of brine shrimps at 100 ug/ml after a 24-hour exposure. Piper betle L. leaf crude extract has an antimicrobial activity aginst Staphylococcus aureus, bacillus subtilis and Escherichia coli, although not as effective as the positive control, Mefenamic Acid. In female mice however, the leaf extract was more efficient in reducing pain than the positive control. The results also showed that Piper betle L. leaf crude extract does not have antipasmodic property. (p)Piper betle L. leaf was confirmed to be indeed a medicinal plant, primarily as an analgesic or pain reliever. It can be toxic at concentrations higher than 100 ug/ml.